(untitled) - Cowie, J. M. G. (Boca Raton, 2008)
Maintaining the mission of providing students with a relatively inexpensive introductory text on polymer science that illustrates the interdisciplinary nature of the subject, Cowie (editor of the journal Polymer) and Valeria Arrighi (chemistry, Heriot-Watt U., UK) present the third edition of a volume that first appeared in 1973, which has been updated to provide coverage of recent advances in various areas of the field. It now includes discussion of the control over molecular weight, macromolecular structure and architecture, controlled radical polymerizations, metallocene chemistry, preparation of block and graft copolymers, and preparation of multiarmed and dendritic structures. It also has expanded the discussion of areas where polymeric materials can be used in electronic, biological, and medical applications and has added series of problems to each chapter.
Keywords: Polymers,Polymerization,Hóa học hữu cơ